PTU-072 A UK standardised cystic duct identification technique will help to mitigate the effect of human error and improve systematic training. (28th May 2012) - Brown, C; Radwan, R; Rasheed, A
Abstract : Introduction: Laparoscopic cholecystectomy is a visual discipline and biliary tract anatomy is deduced by visual clues from a displayed image on a TV Screen where errors stemming from visual illusions and misperceptions are possible and even when irregularities were identified, corrective feedback does seem to occur, which is characteristic of human thinking under firmly held assumptions lead to misidentification of the bile duct as a cystic duct and consequent misadventure. Our aim was to survey descriptive terms of cystic duct identification and compare them against the Society of the American Gastrointestinal and Endoscopic Surgeons recommendations being the only written guidance in the literature. Methods: Welsh trainees and ALS members were invited to complete a online survey to select the descriptive terms that best fit their method of cystic duct identification including Calot's triangle Identified", "Calot's triangle Demonstrated", "Infundibular technique utilized" and "Critical View of safety demonstrated". Results: 133 surveys were completed by six clinical fellows (4.5%), 28 ST/SpRs (21.2%) and 98 consultants (74.2%). The most common descriptive terms used was "Calot's triangle demonstrated" (38.3%), followed by "Calot's triangle identified" (32.5%), "critical view of safety demonstrated" (24.2%) and lastly "infundibular technique utilized" (5%). The majority of surgeons in this survey do not seem to select the terms that are perceived to reflect "best practice" for the method of cystic duct identification during LC. It is possible that these surgeons are utilising "best practice" but did not recognise the provided terms or selected the incorrect term or used other terms that were not provided in this survey. Conclusion: The survey highlights the need for standardisation of image-guided surgical procedures to mitigate the effect of human error and take the outcome of such surgery a new height that was never reached in the open era. Standardisation will also permit systematic training and streamline competency testing paving the way for the transition from apprenticeship-based training to a systematic time-efficient training. In the aviation industry the initial study into human factors was controversial but is now a mandatory and cornerstone process for achieving best air transport safety. We feel there is potential for adopting a similar approach in the rapid and technologically advancing era of surgery based on "visual disciplines" to help reduce human error and thus leading to improved patient safety. Competing interests: None declared. Reference: 1. Sockeel P, Chatelain E, Massoure MP, et al. Surgeons can learn from pilots. J Chir (Paris) 2009;146 :250–5.